Bases metabólicas do crescimento muscular - Manda, Rodrigo Minoru [UNESP]; Maestá, Nailza [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2010)
The skeletal-muscle is the largest tissue in the body with the major roles in kinetics and metabolic process. Myogenesis is the consequence of of myogenic over myostatic factors. The hypertrophic growth occurs in myofibrillar diameter and length by predominating protein synthesis over protein breakdown. Protein synthesis is finely controlled by kinase cascade having mTOR as central role. mTOR controls the protein synthesis initiation complex, being influenced positively by muscle contraction, growth factors and also by leucine. Muscle energy deprivation (↑ AMP/ATP) inhibits mTOR by increasing AMPK. Muscle protein synthesis is enhanced by cell hydrating factors (glucose, insulin, creatine, BCAA, glutamine). Postinjury skeletal muscle regeneration is characterized by two local subsequent phases. Sooner after injury, the infiltrated and residual macrophages are classically activated. They promote phagocytosis of tissue debris while preventing early myogenic differentiation. Then macrophages switch their phenotype to sort out inflammation and support myogenesis and myofiber growth.

O músculo esquelético é o maior tecido do corpo e guarda relação com a autonomia somatocinética e homeostase metabólica. A miogênese é decorrente da predominância de fatores protéicos miogênicos sobre miostáticos. O crescimento ocorre predominantemente de forma hipertrófica, após o nascimento, pelo predomínio da síntese sobre o catabolismo protéico. A síntese protéica é finamente mantida por cascata de quinases controladas ou controladoras da mTOR. A mTOR controla o complexo iniciador da síntese protéica, sendo influenciada pela contração muscular, fatores de crescimento e a leucina. O estado de privação energética (↑ AMP/ATP) inibe a mTOR pelo aumento da AMPK. A síntese protéica miofibrilar é estimulada por fatores hidratantes celulares (glicose, insulina, creatina, BCAA, glutamina). Seguindo-se a lesão e necrose miofibrilar, há resposta inflamatória e ação dos fagócitos, promovendo a fagocitose tecidual. Posteriormente, os macrófagos alteram seu fenótipo para resolver a inflamação e promover a miogênese e crescimento miofibrilar.
Metabolic basis of muscle growth
Keywords: Skeletal muscle; Muscle hypertrophy; Protein anabolism; mTOR; Muscle regeneration; Músculo esquelético; Hipertrofia muscular; Anabolismo protéico; mTOR; Regeneração muscular